A Working Brain, A Weary Heart: A Reflection of College Student Well-Being - Dini Nazlianda Panjaitan; Yenni Safitri; Tri Andini; Sandi Pradana (SocioSphere: Interdisciplinary Journal of Social Sciences and Humanities, 2025)
Building balance and maintaining mental health in the waves of challenges faced by students is an important issue that requires serious attention. The level of student stress is closely related to the motivation to learn and the academic pressure they experience in campus life. This includes developing awareness and skills to face challenges and maintain emotional balance. The method we use is a descriptive qualitative method that aims to understand students’ perceptions of a particular phenomenon. Data collection techniques are carried out using semi-structured interview guidelines so that the data obtained are more focused and in-depth. The data sources used in this study were students of UIN Syekh Ahmad Addary Padangsidimpuan. Students use various strategies to maintain their mental well-being, ranging from being active, such as exercising, worshiping, and managing time, to telling close friends and family and seeking social support. Strengthening social support is also an important solution. Campuses need to build supportive communities through the formation of discussion groups, support groups, or healthy student organization activities. Students from difficult economic backgrounds must also receive special attention through adequate social scholarships and financial assistance. The results of the study show that many students face high mental and emotional burdens, which have an impact on learning motivation, social relations, and mental health. This study emphasizes the importance of institutional support and a campus environment that is responsive to students’ psychosocial needs in order to create a more humane and sustainable educational ecosystem.